(untitled) (Experimental biology, 2016)
The review discusses the prospects for the use of chemical mutagenesis to produce crops with valuable traits. The development of effective biotechnology-based mutagenesis for use in breeding new cultivars of produce is very important for Kazakhstan as a zone of risky agriculture. The article gives examples where the traditional use of mutant strains in the selection process, including their incorporation into hybridization has great potential in creating cultivars. At the same time, to increase the effectiveness of induced mutagenesis in selection can be by the use of cell culture and tissue. The in vitro culture is the most promising use of isolated microspores. The use of chemical mutagens open new perspectives in basic research on the study of the functions of plant genes.